Paul the Cosmopolitan?. (January 2020) - Stanley, Christopher D.
Abstract : The apostle Paul has been viewed by many as a cosmopolitan thinker who called Christ-followers to embrace the ideal of a single humanity living in harmony with a divinely ordered cosmos. A close comparison of Paul's apocalyptic theology with various interpretations of 'cosmopolitanism' over the centuries, however, shows few points of agreement. Paul was fundamentally a Jewish sectarian whose vision for a better world embraced only Christ-followers and involved the cataclysmic end of the present world order. Those who accepted and lived by this vision were effectively relegated to the same marginal position in civic life as the local Jewish community.